Effect of different implant positions for two implant-retained mandibular overdenture: a retrospective 5-years radiographic evaluation of the circumferential peri-implant bone loss and posterior ridge resorptive changes - Khloud Ezzat Mourad; Radwa Mohsen Kamal Emera; Ahmed Habib (BMC, 2024)
Abstract Background Studies did not recommend which position for implant overdenture poses the lowest biomechanical risk and the least chance of peri-implant bone loss and ridge resorption for those who might need a mandibular two-implant overdenture. The study objectives were to investigate the impact of implant position, in lateral incisors or canine positions, on peri-implant bone loss and posterior ridge resorption. Methods Fifty patients with mandibular two-implants were recalled and divided according to the implant position into two groups (group L: implants in lateral incisor positions and group C: implants in canine positions). The circumferential peri-implant bone level and posterior ridge resorption were assessed at implant insertion (T0), one year later (T1), and five years later (T5) using the follow-up CBCT. Data were analyzed using the Statistical Package of Social Science (SPSS) program. A Mann-Whitney test was used to compare two different groups. Paired groups were compared using the Wilcoxon signed-rank test. The threshold of significance is fixed at a 5% level (p-value). Results Significant differences in the vertical bone loss between groups appeared at (T5 - T1) (Mann Whitney test, (P = 0.01)) and at (T5 - T0) (Mann Whitney test, (P = 0.005)), and a significant difference in horizontal bone loss between groups was found at (T1 - T0) (Mann Whitney test, (P = 0.041)) and (T5 - T1) (Mann Whitney test, (P = 0.041)). Also, there were significant differences over the evaluation period between groups at certain points along the ridge at M1 (Mann Whitney test, (P = 0.021)), M3 (Mann Whitney test, (P = 0.008)), and M4 (Mann Whitney test, (P = 0.015)). Conclusions According to the findings of this clinical study, the placement of implants in the lateral incisor position for two implant-retained overdentures is a viable choice. In comparison to the canine position, the lateral incisor position demonstrated superior peri-implant responses, which could potentially enhance the longevity of the implants. Furthermore, the placement of implants in the lateral incisor position can promote a more even distribution of stress and help mitigate posterior ridge resorption. Conversely, implants in the canine position may cause a seesaw effect and result in greater posterior ridge resorption. Clinical Trial Registry Number (NCT06055842) (13/03/2024).